Statistic Value for Determination of Parents-child Relationship using Single Nucleotide Polymorphisms (SNPs) 44 Loci in Thai Individuals (Indian Journal of Forensic Medicine & Toxicology, 2022)
The current report determined the the parent-child relationship based upon 44 SNPs markers by iPLEX® ProSample ID Panel using statistic values of paternity index (PI). The sample study had two groups: True parent-child(n= 38 families) and unrelated groups (n=38 families). The results showed that the true parent-child group shared44 loci (38 families: 100%), and the unrelated groups had loci mismatch between 2 to 13 loci. The four mismatchloci was the highest number of families (10 families: 26.32%). The maximum and minimum of PI values were1.0120x107 and 83.9371 were among the true parent-child groups. The unrelated group’s maximum and minimumPI values were 5.0065x104 and 7.0750, respectively. The lower limit of the distribution of the true parent-childintersected with the upper limit of the distribution of the unrelated between the values of 83.9371 to 5.0065 × 104. Inthis range of values, the distribution of the PI values could not be used to determine the relationship and thereforewas recognized as a “gray zone”. However, if eliminated mismatch for calculating relatedness of PI, it made thegray zone not allow for clear identification. This research showed that the difference between true parent-childand unrelated groups using 44 SNPs loci typing could help predict human relationships and be applied in otherrelationships in the future.
Keywords: SNPs, Parents-child, Paternity index